IMPLEMENTASI PROGRAM KELUARGA SADAR GIZI (KADARZI) DI KOTA PEKANBARU - Delfi Susanti; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is based on the phenomenon of many steps of implementation activities of Nutrition Conscious Family Program (Kadarzi) not running optimally in Pekanbaru City. Implementation of Kadarzi program at Pekanbaru Regency/City level is coordinated and become the responsibility of Pekanbaru Municipal Health Department, and is implemented by all Community Health Center and nutrition cadres in all subdistricts in Pekanbaru City. This research aims to know how Implementation of Nutrition Family Program (Kadarzi) in Pekanbaru City and to know what factors affect the Implementation of Nutrition Family Program (Kadarzi) in Pekanbaru City. The type of research used is descriptive qualitative. Data collection techniques are done through observation, interviews, documentation,and literature techniques and all information is collected , analyzed , and studied to become a unified whole. The location of research in this study is Health Office of Pekanbaru City, Pekanbaru City Health Office is the agency which responsible for Implementation of Nutrition Conscious Family Program (Kadarzi) in Pekanbaru City. Data analysis techniques used in this research are descriptive qualitative data analysis. The results showed that Implementation of Nutrition Family Conscious Program (Kadarzi) in Pekanbaru City is not optimal. This can be seen from several steps of activity as follows: Arranging activity planning for achievement of target Kadarzi either through APBN, APBD and other source is not maximal yet, Implementation of advocacy, dissemination of information continuously not implemented maximally, Implementing dissemination of information through various media not yet optimal and not sustainable, Implement monitoring, coaching and technical guidance and evaluation still need to be improved. Factors influencing the Implementation of Nutrition Conscious Family Program (Kadarzi) in Pekanbaru City are Dissemination of information by the Public Health Service to the community related to Nutrition Awareness Program (Kadarzi) are still very less and not maximal, Quantity or amount of Human Resources in Kadarzi program exactly nutrition executive and nutrient cadres still need tob added due to lack of nutrition experts both in the Health Office, Community Health Centre and Cadres. Keywords: Implementation, Program, Kadarzi